Odškodninske terjatve iz delovnega razmerja v novejši sodni praksi - Debelak, Marijan (Delavci in delodajalci, 2014)
The paper addresses some issues in relation to damage claims arising from the employment relationship in the light of recent case law. Regarding the issue of limitation periods, the author draws attention to the distinction between typical claims from employment relationship and compensation claims for accidents at work or (occupational) disease. The article presents the current practice with regard to tort or contractual liability in case of unlawful termination of employment contract which may be questionable and then the possibility to withdraw compensation claims arising from employment relationship and some of the issues related to compensation for breach of the competition prohibition and competition clause.
Keywords: delovna razmerja; odškodnina; odškodninska odgovornost; terjatve